Women in the ancient Mediterranean world - Middleton, Guy D. (Cambridge, UK ; New York, NY)
xix, 294 sayfa
Keywords: “In this book, Guy D. Middleton explores the fascinating lives of thirty real women of the ancient Mediterranean from the Palaeolithic to the Byzantine era. They include queens and aristocrats, such as the Pharoah Hatshepsut and the Etruscan noblewoman Seianti; Eritha and Karpathia, Bronze Age priestesses from the Aegean; a Pompeiian prostitute called Eutychis; the pagan philosopher Hypatia and the Christian saint Perpetua, from North Africa, as well as women from smaller communities. Middleton uses a wide range of archaeological and historical evidence, including burials and funerary practices, graffiti, inscriptions and painted pottery, handprints, human remains and a variety of historical texts, as well as the latest modern research. His volume weaves together the stories of real women, placing them firmly in the spotlight of history. Engagingly written and up-to-date in its scholarship, Middleton's book offers new insights for students and researchers in Ancient History, Archaeology and Mediterranean Studies, as well as in Women's History.“ --